Roger Machado, um português ao serviço dos primeiros soberanos Tudor - Francisco Leitão (Medievalista)
The article analyses the life and diplomatic activity of Roger Machado, the Portuguese diplomat who served the English kings between the late XVth and the early XVIth centuries. The main focus is placed upon the diaries written by himself as testimony of the embassy of 1490 to the Catholic Kings of Spain and João II of Portugal. The documents are framed within the diplomatic relations of these countries and can be of use to shed light over the daily life of late medieval diplomacy.